2008
DOI: 10.2152/jmi.55.37
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mediastinal lymph nodes sampling in patients with clinical stage I non-small cell lung cancer

Abstract: :Objective : Systematic nodal dissection has been recommended for patients with resectable non-small cell lung cancer because of its staging accuracy. However, in patients with clinical stage I non-small cell lung cancer whether systematic nodal dissection provides more benefits than mediastinal lymph node sampling or not is controversial. In this retrospective study, we evaluated the effect of mediastinal lymph node sampling in patients with clinical stage I NSCLC. Methods : One hundred and nineteen consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Some scholars have even advocated a localized segmentectomy or a wedge resection instead of the standard lobectomy plus lymph node dissection for cases with high GGO. [11] In addition, our study also found that the closer the tumor lied to the hilum, the easier mediastinal lymph node metastasis occurs. In our opinion, as there is no patient can be absolutely excluded the presence of N2 currently, a sentinel frozen biopsy can be conducted during the operation of T1a NSCLC.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Some scholars have even advocated a localized segmentectomy or a wedge resection instead of the standard lobectomy plus lymph node dissection for cases with high GGO. [11] In addition, our study also found that the closer the tumor lied to the hilum, the easier mediastinal lymph node metastasis occurs. In our opinion, as there is no patient can be absolutely excluded the presence of N2 currently, a sentinel frozen biopsy can be conducted during the operation of T1a NSCLC.…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, lobe-specific dissection can be a better choice for lymph node dissection for T1a NSCLC. [4,11] In addition, our study showed that the cases with high proportion of GGO had no recurrence and the prognosis is good during the five years' follow-up. A further analysis of the cases in SL group showed that none of the 16 cases with high proportion of GGO had mediastinal lymph node metastases.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The study of Takizawa and colleagues failed to prove any significant difference in overall survival between the MLND and the MLNS groups in 119 patients with clinical stage I NSCLC. 22 After the median follow up of 79 months, the survival rate was 78% in the MLND group and 76.2% in the MLNS group (P=0.6).…”
Section: Resultsmentioning
confidence: 88%
“…Anatomic lung resections with systematic lymph node dissection have become the recommended treatment for early stage nonsmall lung cancer (NSCLC) [1] . Many investigators and clinicians recommend systematic nodal dissection to all lung cancer patients except those with clinical stage I disease [2] .…”
Section: Introductionmentioning
confidence: 99%